PERUBAHAN PERILAKU KECERDASAN EMOSIONAL ANAK USIA DINI MELALUI PENDIDIKAN SENI TARI - Kusumastuti, Eny (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2009)
Education with a dimension of EQ (Emotional Quotions) can be found in theconcept of dance education. This study examined how the implementationprocess, and changes in emotional intelligence behaviour of young childrenthrough learning the art of dance. The approach is qualitative. Data collectiontechniques used interviews, participant observation, and studydocumentation. Techniques of data analysis used reducing, clarifying,describing, concluded, and interpret all the information selectively. The resultsshowed that the process of implementation of dance education in earlychildhood can not be separated from teaching and learning process, whichincludes: objectives, teaching materials, teaching methods and learningactivities, facilities and infrastructure, evaluation, social and culturalconditions. Emotional intelligence behaviour change early childhood throughlearning the art of dance can be seen through: (1) a sense of pride, (2) has abrave nature, (3) able to control emotions, (4) able to hone refinement, (5) beable to nurture a sense of responsible, (6) able to nurture a sense of self, (7) easyto interact with others, (8) has a good performance, (9) are able to developimagination, and (10) becomes a creative child.Kata Kunci : pendidikan seni tari, kecerdasan emosional, anak usia dini.